2021
DOI: 10.1038/s41598-021-86948-y
|View full text |Cite
|
Sign up to set email alerts
|

Separating individual contributions of major Siberian rivers in the Transpolar Drift of the Arctic Ocean

Abstract: The Siberian rivers supply large amounts of freshwater and terrestrial derived material to the Arctic Ocean. Although riverine freshwater and constituents have been identified in the central Arctic Ocean, the individual contributions of the Siberian rivers to and their spatiotemporal distributions in the Transpolar Drift (TPD), the major wind-driven current in the Eurasian sector of the Arctic Ocean, are unknown. Determining the influence of individual Siberian rivers downstream the TPD, however, is critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 64 publications
4
40
1
Order By: Relevance
“…The two crossings showed small differences in the slopes of the correlations, which might be due to contributions of different Eurasian rivers. Paffrath et al (2021) indeed showed, using Nd isotopes and concentrations, that the contribution of the different Siberian rivers varies between the stations and with depth, potentially also explaining the variation in metals. The Nd isotope-based river signals can still be distinguished in the TPD and down to ∼100 m water depth with a vertical and lateral separation of Lena water in the Laptev Sea shelf water overriding Yenisei/Ob water in Kara Sea shelf water.…”
Section: The Influence Of the Tpdmentioning
confidence: 78%
See 2 more Smart Citations
“…The two crossings showed small differences in the slopes of the correlations, which might be due to contributions of different Eurasian rivers. Paffrath et al (2021) indeed showed, using Nd isotopes and concentrations, that the contribution of the different Siberian rivers varies between the stations and with depth, potentially also explaining the variation in metals. The Nd isotope-based river signals can still be distinguished in the TPD and down to ∼100 m water depth with a vertical and lateral separation of Lena water in the Laptev Sea shelf water overriding Yenisei/Ob water in Kara Sea shelf water.…”
Section: The Influence Of the Tpdmentioning
confidence: 78%
“…Due to their different salinities, the different shelf waters do not mix along the transport toward the Fram Strait. Rare earth elements (Paffrath et al, 2021) had lower concentrations at St 101 (Makarov Basin) compared to the other sampled station (St 125 [Amundsen Basin] and St 96 [Makarov Basin]), and Nd isotopes, in combination with sea-ice melt corrected salinities, indicated the presence of Lena River and likely Yenisei/ Ob River contributions. However, even though for the metals more stations were sampled such clear differentiation could not be observed in the trace metals distributions, but nevertheless the different riverine endmembers likely contributed to the observed variation in trace metal concentrations in the TPD.…”
Section: The Influence Of the Tpdmentioning
confidence: 90%
See 1 more Smart Citation
“…The only Si isotope data from the Mackenzie River are from a single study conducted during summer (Pokrovsky et al, 2013). The reported average δ 30 Si of +1.36 ± 0.19 is comparable to values in Eurasian rivers on the Siberian Shelf from the same season, when δ 30 Si values tend to be 0.5-1.0 higher than during peak flow (Pokrovsky et al, 2013;Sun et al, 2018;Paffrath et al, 2021). Those data suggest that differences in Si isotopic composition of the freshwater end members cannot explain the difference in slopes as the Mackenzie River appears to have a Si isotope composition similar to the Lena River that was the dominant influence on the TPD during GN01 (Paffrath et al, 2021).…”
Section: The Polar Mixed Layer Of the Central Arctic Oceanmentioning
confidence: 81%
“…Those differences may arise from a combination of a strong river influence on Drift waters combined with active Si(OH) 4 consumption on shelves. Paffrath et al (2021) note that in 2015 the TPD was heavily influenced by the Lena River and secondarily by the Yenisei and Ob Rivers based on dissolved neodymium isotopes and rare earth element concentrations. These rivers have high dissolved Si content (discharge-weighted average annual concentrations of 66, 93, and 81 µmol kg −1 for the Lena, Ob, and Yenisei Rivers, 2020) estimate that [Si(OH) 4 ] in the source waters feeding the TPD sampled during GN01 was 47 µmol kg −1 which would represent the net result of river inputs, benthic efflux, mixing, and biological consumption on the Eurasian shelf.…”
Section: The Polar Mixed Layer Of the Central Arctic Oceanmentioning
confidence: 99%